Water dynamics at the nanoscale - Masciovecchio, C.; Bencivenga, F.; Gessini, A. (Condensed Matter Physics, 2008)
The recent construction of an Inelastic UltraViolet Scattering (IUVS) beamline at the ELETTRA Synchrotron
Light Laboratory opens new possibilities for studying the density fluctuation spectrum, S(Q,E), of disordered
systems in the mesoscopic momentum (Q) and energy (E) transfer region not accessible by other spectroscopic
techniques. As an example of possible application of IUVS technique we will discuss the new insights
provided in the case of water dynamics. From the analysis of IUVS spectra we were able to measure the temperature
and pressure dependencies of structural relaxation time (τ) in water. In the case of room-pressure
water the values of τ, as derived by IUVS, are fairly consistent with previous determinations and, most important,
its temperature dependence agrees with Mode Coupling Theory (MCT) predictions. Moreover we found
that τ decreases with increasing pressure at fixed temperature. The observed trend demonstrates that the
structural relaxation phenomenology is strongly affected by the applied pressure. However, further investigations
are necessary in order to clarify the physical meaning of these preliminary experimental results. Недавня побудова лiнiї непружнього розсiяння ультрафiолетових променiв (НРУП) у синхротроннiй лабораторiї ELETTRA вiдкриває новi можливостi для дослiдження спектру флуктуацiй густини, S(Q,E), у невпорядкованих системах у мезоскопiчнiй областi передачi iмпульсу (Q) та енергiї (E), яка є недоступною для iнших спектроскопiчних методик. Як приклад можливого застосування методу НРУП ми обговорюємо новi результати для випадку динамiки води. З аналiзу спектрiв НРУП ми мали можливiсть вимiряти залежнiсть вiд температури та тиску для часу структурної релаксацiї (τ) у водi. Для випадку нормального тиску значення τ, визначене з НРУП, добре узгоджується з попереднiми розрахунками та, що є бiльш важливо, його температурна залежнiсть узгоджується з передбаченнями теорiї взаємодiючих мод. Крiм того, ми знайшли, що τ зменшується зi зростанням
тиску при фiксованiй температурi. Спостережувана тенденцiя демонструє, що явище структурної релаксацiї має сильну залежнiсть вiд прикладеного тиску. Однак, для того, щоб вияснити фiзичне значення цих попереднiх експериментальних результатiв, необхiднi подальшi дослiдження.